PERSEPSI MASYARAKAT DKI JAKARTA TENTANG PEMBERITAAN PENANGANAN WABAH COVID-19 DI WILAYAH DKI JAKARTA - Aminudin, Amin (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
Handling of COVID 19 Cases in the DKI Jakarta area is quite a concern of the Indonesian public. Jakarta as epicentrum of Indonesia's control is also the Epicentrum of the spread of the COVID-19 virus. So that the information that appears in the mass media is in line with the increasing popularity of Anis Baswedan as Governor of DKI Jakarta. Governor Anies' popularity in the mass media is increasing due to his performance and ability to predict and deal with the COVID-19 outbreak. The goal to be achieved from this study is to find out how the perception of the people of DKI Jakarta about the mass media in reporting strategies for handling the COVID-19 outbreak by the DKI Jakarta Regional Government. 2. To find out how the strategy of handling the COVID-19 outbreak by the DKI Jakarta Regional Government towards the formation of public opinion of DKI Jakarta residents. This research uses a kualiitative approach with perception theory, descriptive qualitative approach with interview methods as an instrument of primary data collection and literature study as secondary material the subject of this study is DKI Jakarta Residents scattered in the regency / city area in DKI Jakarta Province. . The results of this study show that the public tends to follow the mainstream of mass media or can be said to have a high enough confidence in the information disseminated by the mass media about the handling of the COVID-19 pandemic carried out by the Jakarta Provincial Government. Jakarta Provincial Government which is considered good by the mass media. good by the public along with the high intensity of mass media consumption.